Understanding Adolescent-Parent Interpersonal Relationships in Youth Sports: A Mixed-Methods Study - Ausra Lisinskiene; Timothy Guetterman; Saulius Sukys (MDPI AG, 2018)
The purpose of this study was to examine the relationship between participation in youth sport and adolescent–parent attachment. A mixed-method explanatory sequential study design was applied. In the first phase, 648 adolescent athletes and non-athletes completed the Inventory of Parent and Peer Attachment–Revised (IPPA–R). In the second phase, 15 adolescent athletes took part in semi-structured interviews. In the first, quantitative phase, three factors were predictors of adolescents’ attachment to parents and peers: trust, communication, and alienation. In the qualitative follow-up, three themes emerged: adolescents’ attachment to the sport; adolescent–parent attachment; adolescents’ thoughts about parents. The analysis of the adolescent–parent interpersonal relationship revealed that athlete adolescents’ relations and attachment to parents compared to non-athlete adolescents are more intensively expressed in all scales: trust, communication and alienation. Interviews with adolescent athletes revealed that parent–adolescent interpersonal relationship and attachment to parents is more important at the early period of sporting life, and becomes less appreciable or unwelcome when children gain sporting experience. The study indicated that the form and degree of parental involvement in children’s sporting activities impacts the effectiveness of parent–athlete interpersonal relationships. The degree and the form of parental involvement in children’s sports chosen by the parents are not always appropriate and encouraging, and they are not always supportive of adolescents’ opinions.